At the end of the day / Harmeet Singh Kuldip Singh - Kuldip Singh, Harmeet Singh (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.